Intestinal toxicity and resistance gene threat assessment of multidrug-resistant Shigella: A novel biotype pollutant. (1st January 2023) - Zhao, Jianbin; Zhang, Chaonan; Xu, Yanbin; Li, Xinyan; Lin, Xiaojun; Lin, Zitao; Luan, Tiangang
Abstract: Multidrug-resistant bacteria, especially pathogens, pose a serious threat to disease treatment and recovery, but their potential toxicity to animal development is not entirely clear. As the most important site for nutrient absorption, we studied the intestinal microbiome of Xenopus tropicalis by analyzing the effect of multidrug-resistant Shigella on its intestinal health. Unlike in the control, Shigella intake promoted the secretion of neutral mucus and inhibited intestinal development and weight gain. Following 60 days of exposure, intestinal crypt atrophy, intestinal villus shortening, internal cavity enlargement, and external mucosal muscle disintegration were observed. The circular and longitudinal intestinal muscles became thinner with increasing pathogen exposure. In addition, the presence of Shigella altered the expression of multiple cytokines and classic antioxidant enzyme activities in the gut, which may have caused the intestinal lesions that we observed. 16 S rDNA sequencing analysis of intestinal samples showed that exposure to Shigella destroyed the normal gut microbial abundance and diversity and increased the functional bacterial ratio. Notably, the increased abundance of intestinal antibiotic resistance genes (ARGs) may imply that the resistance genes carried by Shigella easily migrate and transmit within the intestine. Our results expand existing knowledge concerning multidrug-resistant Shigella -induced intestinal toxicity in X. tropicalis and provide new insights for the threat assessment of resistance genes carried by drug-resistant pathogens. Graphical abstract: Image 1 Highlights: Shigella can be colonized in the intestinal tract of X. tropicalis in a short time. Shigella caused intestinal lesions due to oxidative stress and cytokine disorders. Intestinal secretion and dysbacteriosis induced by chronic exposure to Shigella . Shigella may increase intestinal ARGs abundance by accelerating RGs migration.